Distribution, composition and functions of gelatinous tissues in deep-sea fishes. Issue 12 (6th December 2017) - Gerringer, Mackenzie E.; Drazen, Jeffrey C.; Linley, Thomas D.; Summers, Adam P.; Jamieson, Alan J.; Yancey, Paul H.
Abstract : Many deep-sea fishes have a gelatinous layer, or subdermal extracellular matrix, below the skin or around the spine. We document the distribution of gelatinous tissues across fish families (approx. 200 species in ten orders), then review and investigate their composition and function. Gelatinous tissues from nine species were analysed for water content (96.53 ± 1.78% s.d.), ionic composition, osmolality, protein (0.39 ± 0.23%), lipid (0.69 ± 0.56%) and carbohydrate (0.61 ± 0.28%). Results suggest that gelatinous tissues are mostly extracellular fluid, which may allow animals to grow inexpensively. Further, almost all gelatinous tissues floated in cold seawater, thus their lower density than seawater may contribute to buoyancy in some species. We also propose a new hypothesis: gelatinous tissues, which are inexpensive to grow, may sometimes be a method to increase swimming efficiency by fairing the transition from trunk to tail. Such a layer is particularly prominent in hadal snailfishes (Liparidae); therefore, a robotic snailfish model was designed and constructed to analyse the influence of gelatinous tissues on locomotory performance. The model swam faster with a watery layer, representing gelatinous tissue, around the tail than without. Results suggest that the tissues may, in addition to providing buoyancy and low-cost growth, aid deep-sea fish locomotion.